Membangun Jiwa Sociopreneurship Masyarakat Desa Rasau Jaya 2 Berbasis E-Marketing Sebagai Media Pemasaran Produk Hasil Pertanian - Ichsan Ichsan; Revi Sesario; Dodi Radiansah; Adi Marjani; Thomas Candra; Nur Fajar (Politeknik Negeri Pontianak, 2021)
Rasau Jaya 2 is a village in the Rasau Jaya District which has a variety of agricultural products. Agricultural products include coconut, hybrid coconut, oil palm, biopharmaceutical crops, fruits and vegetables. The purpose of this activity is to help the community of Rasau Jaya 2 Village market their agricultural products based on e-marketting. The method used is to provide training for the youth of Rasau Jaya 2 Village with e-marketting based marketing. The result of the training is that all participants are satisfied with the online-based product marketing training. Keywords: Sociopreneurship, Rasau Jaya 2 Village, E-Marketing, Product Marketing Media, Agricultural Products